Participatory archives : theory and practice - Benoit, Edward, III; Eveleigh, Alexandra (Facet Publishing, 2019)
The rise of digitisation and social media over the past decade has fostered the rise of participatory and DIY digital culture. Likewise, the archival community leveraged these new technologies, aiming to engage users and expand access to collections. This book examines the creation and development of participatory archives, its impact on archival theory, and present case studies of its real world application. Participatory Archives: Theory and practice is divided into four sections with each focused on a particular aspect of participatory archives: social tagging and commenting; transcription; crowdfunding; and outreach & activist communities. Each section includes chapters summarizing the existing literature, a discussion of theoretical challenges and benefits, and a series of case studies. The case studies are written by a range of international practitioners and provide a wide range of examples in practice, whilst the remaining chapters are supplied by leading scholars from Australia, Canada, Denmark, the Netherlands, Norway, the United Kingdom, and the United States. This book will be useful for students on archival studies programs, scholarly researchers in archival studies who could use the book to frame their own research projects, and practitioners who might be most interested in the case studies to see how participatory archives function in practice. The book may also be of interest to other library and information science students, and similar audiences within the broader cultural heritage institution fields of museums, libraries, and galleries.